2003
DOI: 10.1046/j.1460-9568.2003.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

PACAP and NGF regulate common and distinct traits of the sympathoadrenal lineage: effects on electrical properties, gene markers and transcription factors in differentiating PC12 cells

Abstract: To determine the possible role of pituitary adenylate cyclase-activating polypeptide (PACAP) in the development of the sympathoadrenal cell lineage, we have examined the effects of this neurotrophic peptide, in comparison to nerve growth factor (NGF), on the morphology, electrophysiological properties, expression of neuronal and neuroendocrine marker genes, and activity of transcription factors during differentiation of sympathoadrenal-derived cells, using the rat pheochromocytoma PC12 cell model. Both PACAP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 57 publications
2
49
0
Order By: Relevance
“…Accordingly, PAC1-R has been shown to mediate the effect of PACAP on catecholamine secretion in normal and tumoral sympathetic neurons (Taupenot et al 1998, Ghzili et al 2008. In addition, the prodifferentiating effects of PACAP are mediated through PAC1-R (Grumolato et al 2003b). Therefore, PACAP and its PACAP-preferring receptor PAC1-R are probably involved in the pathophysiology of pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, PAC1-R has been shown to mediate the effect of PACAP on catecholamine secretion in normal and tumoral sympathetic neurons (Taupenot et al 1998, Ghzili et al 2008. In addition, the prodifferentiating effects of PACAP are mediated through PAC1-R (Grumolato et al 2003b). Therefore, PACAP and its PACAP-preferring receptor PAC1-R are probably involved in the pathophysiology of pheochromocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NGF can regulate membrane excitability (Rudy et al, 1987;Toledo-Aral et al, 1995;Levine et al, 1995;Lesser et al, 1999;Grumolato et al, 2003) but its possible role as neuromodulator of brain synaptic plasticity has been debated for a long time. Although NGF perfusion in hippocampal slices (Tancredi et al, 1993) has been reported to block the long-term potentiation (LTP) appearance, other papers have shown no NGF effects on hippocampal and visual cortex plasticity (Khang and Schuman, 1995;Figurov et al, 1996;Akaneya et al, 1997) Moreover, local TrkA activation in primary visual cortex (Pizzorusso et al, 1999) and in vivo NGF injection into the lateral ventricles (Maffei et al, 1992;Lodovichi et al, 2000) counteract the ocular dominance distribution of visual cortical neurons in monocularly deprivated rats.…”
Section: Ngf Bdnf and Synaptic Plasticitymentioning
confidence: 99%
“…Stimulation with differentiating factors, including nerve growth factor (NGF), and the subsequent activation of its receptor, TrkA, were demonstrated to initiate a variety of signaling events which led to the cessation of growth, the acquirement of electrical excitability, the expression of neuron-specific marker proteins, and the extension of neurites (Hagag et al, 1986;Leoni et al, 1999;Grumolato et al, 2003). Neurite extension induced by different stimuli was determined to be a distinctive aspect of neuronal differentiation (Bouron et al, 1999).…”
Section: Introductionmentioning
confidence: 99%